Hearing silence: non-neutral evolution at synonymous sites in mammals - Chamary, J. V.; Parmley, Joanna L.; Hurst, Laurence D. (Nature reviews. Genetics, 2006)
Contrary to the neutral theory, silent mutations can be under natural selection. This is often seen in organisms from large populations, but the authors present evidence that it also occurs in mammals, because synonymous mutations affect mRNA stability and splicing. Key Points Synonymous mutations in mammals are often assumed to be free from natural selection, not only because such mutations do not alter the encoded protein, but also because neutral theory predicts that when population sizes are small, as they are in mammals, selection should be too weak to act on changes that have relatively small effects on fitness. Recent evidence indicates that synonymous sites in mammals are not always neutrally evolving and numerous examples of disease-associated synonymous mutations now exist. Selection might act on synonymous codon usage to maximize the efficiency of translation, to promote mRNA stability and/or to improve splicing efficiency. In mammals, there is good support for the latter two models, but less for the first possibility. Although non-neutral evolution at synonymous sites means that the genomic mutation rate has been underestimated, it is unlikely to be a source of error that exceeds the uncertainties inherent in the other parameters that are used to estimate the mutation rate. As synonymous sites can be subject to purifying selection, a high K a / K s ratio cannot be assumed to indicate positive selection on a protein. Preliminary studies indicate that the method might be misleading as often as it is correct. Knowing why some synonymous sites are functional allows us to better understand how codon choice might be manipulated to increase the efficacy of transgene expression, especially when transgenes have most of their introns removed. Although the assumption of the neutral theory of molecular evolution — that some classes of mutation have too small an effect on fitness to be affected by natural selection — seems intuitively reasonable, over the past few decades the theory has been in retreat. At least in species with large populations, even synonymous mutations in exons are not neutral. By contrast, in mammals, neutrality of these mutations is still commonly assumed. However, new evidence indicates that even some synonymous mutations are subject to constraint, often because they affect splicing and/or mRNA stability. This has implications for understanding disease, optimizing transgene design, detecting positive selection and estimating the mutation rate.